2018
DOI: 10.1177/0300060518762281
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban versus nadroparin for preventing deep venous thrombosis after total hip arthroplasty following femoral neck fractures: A retrospective comparative study

Abstract: ObjectiveThis study was performed to evaluate the efficacy of rivaroxaban versus nadroparin for preventing deep venous thrombosis (DVT) in elderly patients with osteoporosis undergoing initial total hip arthroplasty (THA) for femoral neck fractures.MethodsProspectively maintained databases were reviewed to retrospectively compare elderly patients with osteoporosis who underwent initial THA for femoral neck fractures from 2007 to 2015. The patients received peroral rivaroxaban at 10 mg/day for 2 weeks or subcut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…The process of article selection is presented in Figure 1. Ultimately, five studies were included (34,(39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of article selection is presented in Figure 1. Ultimately, five studies were included (34,(39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 99%
“…All studies predominantly included elderly patients (range of mean ages 65-85 years). One study only included patients with osteoporosis and traumatic hip fractures (42). Two studies included only patients using rivaroxaban, one study included only patients using edoxaban, two studies included patients using various DOACs.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong and his colleagues have shown that the occurrence rate of DVT was about 0.24% in THA, [ 37 ] and Chi et al found that the incidences of DVT were 6.8% and 19.7% with rivaroxaban and nadroparin, respectively. [ 38 ] Charters et al conducted a retrospective cohort study, including 1113 patients received enoxaparin and 649 patients received rivaroxaban after TKA and THA, and found no differences in DVT (1.8% vs 0.9%) and PE (0.7% vs 0.3%). [ 36 ] Beyer-Westendorf and his colleagues found a decrease in symptomatic DVT in 54 of 1495 patients (3.6%) who received enoxaparin compared to 20 of 1043 (1.9%) patients who received rivaroxaban, and PE rates of 0.54% and 0.19% in the enoxaparin and rivaroxaban groups, respectively.…”
Section: Discussionmentioning
confidence: 99%